PRAKTIK AKUNTANSI PADA TOKO TRADISIONAL DI DESA PRENDUAN, KAB. SUMENEP - Asy’ari Asy’ari; Mahwiyah Mahwiyah; Wahidahwati Wahidahwati (STIE Mahardhika, 2020)
SMES are growing in NUMBER, quoted from DINKOP on average SME growth in Indonesia as much as 1, 2jt per year. From here, the author wants to know if the MSME is more focused to the traditional shop located in the village Prenduan – Sumenep accounting or not. Being an attraction for researchers because the village of Prenduan is a very crowded village of SMES from the adjacent villages. This village of business growth is seen rapidly research using qualitative method of diskriptif with 20 informers of the business Pekaku traditional shop with an interview and observation technique. The results of this research shows that there are still many SMES who are not aware of the importance of accounting and lack of a desire to record transactions.